Usos e problemas socioambientais no processo de ocupação territorial sobre a bacia hidrográfica da Cachoeira Grande - Manaus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Throughout history, the rivers of the urban space in Manaus were silted up and polluted. This fact is a reflection of the urban dynamics referring to the phases of a process of socioeconomic development, marked by irregular forms of use and occupation, on hydrographic basins, in different historical periods. Thus, the objective of this research is to analyze the process of territorial transformation in the Cachoeira Grande basin, uses and socio-environmental problems that occurred in the main river of the 20th century in the city of Manaus, called Cachoeira Grande hydrographic basin. To this objective, field visits were added to identify the territorial occupation process determined between time and space production, relating the dynamics of multiple uses of water resources with the disorderly growth and occupation on the banks of the Cachoeira Grande. The methodological approach of this research included: a bibliographic survey for the theoretical framework, field observation to obtain data and aggravated georeferencing of the study area, such as fluvial geomorphology, environmental degradation, socio-environmental conflicts and human occupations and transformations in the landscape. The third stage consists of a descriptive contextual analysis of the results of programs and projects for revitalization and basic sanitation carried out through PROSAMIM, which transformed the quality of housing for the population located on the banks of streams, awakening a reflection on the landscape of the past and present , associating with socio-spatial conflicts, nowadays, derived from the political lack of commitment to environmental preservation. The hydrographic basin of this river was, for a long time, the water reservoir, to supply a city, known as the “Cachoeira Grande” reservoir. Along with other canals, geographically delimited the initial nucleus of formation of the city (currently São Raimundo Basin). The results showed that the study in the Cachoeira Grande basin can contribute to an analysis of the institutional and political context, highlighting the importance and valuation of planning, which can respond to the challenges of minimizing socio-environmental problems and the development of various management instruments able to requalify this water system.
The territorial occupation process of the Cachoeira Grande basin: uses and socio-environmental problems in the context of public policies
Keywords: Bacias hidrográficas - Manaus (AM); Bacias hidrográficas - Aspectos ambientais - Manaus (AM); Desenvolvimento de recursos hídricos - Aspectos ambientais - Manaus (AM); CIÊNCIAS HUMANAS: GEOGRAFIA: GEOGRAFIA HUMANA: GEOGRAFIA URBANA; Bacia hidrográfica; Reservatório; Uso e ocupação; Conflitos socioambientais